2017
DOI: 10.1155/2017/2525967
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Neurodegenerative Diseases: From Molecular Mechanisms to Clinical Applications

Abstract: Increasing numbers of individuals, particularly the elderly, suffer from neurodegenerative disorders. These diseases are normally characterized by progressive loss of neuron cells and compromised motor or cognitive function. Previous studies have proposed that the overproduction of reactive oxygen species (ROS) may have complex roles in promoting the disease development. Research has shown that neuron cells are particularly vulnerable to oxidative damage due to their high polyunsaturated fatty acid content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
500
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 648 publications
(518 citation statements)
references
References 145 publications
(211 reference statements)
8
500
0
10
Order By: Relevance
“…The most common neurodegenerative diseases where resveratrol has shown clinical potential are Alzheimer's disease (AD) and cognitive impairment. Numerous genes and pathways, including oxidative stress and mitochondrial damage, have been implicated in these diseases . Resveratrol plays a major role in neuroprotection by reducing oxidative damage, mitochondrial dysfunction, and chronic inflammation .…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…The most common neurodegenerative diseases where resveratrol has shown clinical potential are Alzheimer's disease (AD) and cognitive impairment. Numerous genes and pathways, including oxidative stress and mitochondrial damage, have been implicated in these diseases . Resveratrol plays a major role in neuroprotection by reducing oxidative damage, mitochondrial dysfunction, and chronic inflammation .…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…Neurons in the brain have an extremely high risk of ROS production and oxidative damage because of their high oxygen consumption and energy production. Given that neurons are susceptible to ROS, it is not surprising that oxidative stress has been widely believed to be associated with the initiation and evolution of many neurodegenerative diseases, such as AD . Gonzalez‐Reyes et al suggested that the excessive production of oxidants by mitochondria result in the loss of brain homeostasis in AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Second, oxidative stress from surgery or anesthesia might be related. It was suggested that patients with SCA have mitochondrial dysfunction, and a previous study found elevated oxidative stress and significant mitochondrial alternations in the Purkinje cells in patients with SCA1 [17]. Third, unrecorded changes such as hypotension, anemia, or anorexia during or after surgery, may damage the brain in manners that are not apparent with imaging.…”
Section: Discussionmentioning
confidence: 99%